The relationships between ACTN3 rs1815739 and PPARA-α rs4253778 gene polymorphisms and athletic performance characteristics in professional soccer players - Celal Bulgay; Ladislav Cepicka; Metin Dalip; Selin Yıldırım; Halil İ. Ceylan; Özlem Ö. Yılmaz; Korkut Ulucan; Georgian Badicu; Mesut Cerit (BMC Sports Science, Medicine and Rehabilitation, 2023)
Abstract Background Current research on athletic performance focuses on genetic variants that contribute significantly to individuals’ performance. ACTN3 rs1815739 and PPARA-α rs4253778 gene polymorphisms are variants frequently associated with athletic performance among different populations. However, there is limited research examining the pre-and post-test results of some variants of athletic performance in soccer players. Therefore, the presented research is to examine the relationships between the ACTN3 rs1815739 and PPARA-α rs4253778 gene polymorphisms and athletic performance improvement rates in adaptations to six weeks of training in elite soccer players using some athletic performance tests. Methodology Twenty-two soccer players between the ages of 18 and 35 voluntarily participated in the study. All participants were actively engaged in a rigorous six-day-a-week training program during the pre-season preparation period. Preceding and following the training program, a battery of diverse athletic performance tests was administered to the participants. Moreover, Genomic DNA was extracted from oral epithelial cells using the Invitrogen DNA isolation kit (Invitrogen, USA), following the manufacturer’s protocol. Genotyping was conducted using real-time PCR. To assess the pre- and post-test performance differences of soccer players, the Wilcoxon Signed Rank test was employed. Results Upon analyzing the results of the soccer players based on the ACTN3 genotype variable, it was observed that there were no statistically significant differences in the SJ (Squat Jump), 30m sprint, CMJ (Counter Movement Jump), and DJ (Drop Jump) performance tests (p > 0.05). However, a statistically significant difference was identified in the YOYO IRT 2 (Yo-Yo Intermittent Recovery Test Level 2) and 1RM (One Repetition Maximum) test outcomes (YOYO IRT 2: CC, CT, and TT, p = 0.028, 0.028, 0.008, 0.000, respectively; 1RM: CC, CT, and TT, p = 0.010, 0.34, 0.001, respectively). Regarding the PPARA-α genotype variable, the statistical analysis revealed no significant differences in the SJ, 30m sprint, CMJ, and DJ performance tests (p > 0.05). Nevertheless, a statistically significant difference was observed in the YOYO IRT 2 and 1RM test results (YOYO IRT 2: CC, CG p = 0.001, 0.020; 1RM: CC, p = 0.000) Conclusions The current study demonstrated significant enhancements in only YOYO INT 2 and 1RM test outcomes across nearly all gene variants following the six-day-a-week training program. Other performance tests, such as the 30m sprint, SJ, CMJ, and DJ tests did not exhibit statistically significant differences. These findings contribute novel insights into the molecular processes involving PPARA-α rs4253778 and ACTN3 rs1815739 that underpin enhancements in endurance (YOYO INT 2) and maximal strength (1RM) aspects of athletic performance. However, to comprehensively elucidate the mechanisms responsible for the association between these polymorphisms and athletic performance, further investigations are warranted. It is thought that the use of field and genetic analyses together to support each other will be an important detail for athletes to reach high performance.